Diversifying crop rotations with pulses enhances system productivity. Issue 4 (14th November 2016) - Gan, Yantai; Hamel, Chantal; Cutforth, Herb; Zentner, Robert P.; Poppy, Lee; O'Donovan, John T.; Campbell, Con A.; Niu, Yining
Abstract : Crop productivity is often limited by availability of water and nutrients, and the challenge is serious in many arid and semiarid regions of the world, including the Northern Great Plains. The objective of this study was to test the hypothesis that diversifying cropping systems with pulse crops can improve the attributes of soil water conservation and soil N benefits and increase total grain production. Earn 1 CEU in Crop Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/790 .